2017
DOI: 10.25165/j.ijabe.20171004.3077
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation and experimental verification on downwash air flow of six-rotor agricultural unmanned aerial vehicle in hover

Abstract: Recently, multi-rotor unmanned aerial vehicle (UAV) becomes more and more significantly irreplaceable in the field of plant protection against diseases, pests and weeds of crops. The easy takeoff and landing performance, hover function and high spraying efficiency of UAV are urgently required to spray pesticide for crop timely and effectively, especially in dispersed plots and hilly mountains. In such situations, the current researches about UAV spray application mainly focus on studying the influence of the U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 15 publications
3
32
0
Order By: Relevance
“…The group including Yang and Xue from Nanjing Research Institute for Agricultural Mechanization continuously focused on multi-rotor CFD. They firstly applied CFD to simulate a six-rotor UAV, SLK-5, and combined with wind-investigation experiments to obtain the characteristics of both maximum entire velocity and Z-direction wind [56] . However, the test error was big (less than or equal to 12%) so that the experimental design and the details of CFD models were required to be optimised.…”
Section: Examination By Using Cfdmentioning
confidence: 99%
“…The group including Yang and Xue from Nanjing Research Institute for Agricultural Mechanization continuously focused on multi-rotor CFD. They firstly applied CFD to simulate a six-rotor UAV, SLK-5, and combined with wind-investigation experiments to obtain the characteristics of both maximum entire velocity and Z-direction wind [56] . However, the test error was big (less than or equal to 12%) so that the experimental design and the details of CFD models were required to be optimised.…”
Section: Examination By Using Cfdmentioning
confidence: 99%
“…In regards to the choice of sUAS flight platform, and optimal integration of sensor to the platform, the effects of the flow field of the sUAS should be further considered. In particular, the effect of the downwash caused by the rotating rotor blades [35,36] can distort the shape (concentration field) of the methane plume, which could then complicate the use of algorithms to infer source mass flow based on the measured flow field. Indeed, future research will focus on inferring mass-flow (and source location) from the sUAS methane concentration maps and wind data [15,[37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…While UAVs are actively deployed for gas monitoring, deficiencies in current UAV-based monitoring equipment still need to be addressed. The UAV propellers can cause airflow disturbance, which will change the concentration of the original gas and PM in conditions without UAV airflow [22][23][24]. Roldan et al found that gas measurements with moving and stationary rotors are different and the average relative errors for temperature, humidity, and CO 2 concentration are 3.71%, 1.65%, and 3.84%, respectively [25].…”
Section: Introductionmentioning
confidence: 99%